Exploring the newly emerging effects of native seagrasses on survival and growth of non-native juvenile clams - Galván, Cristina; Puente, Araceli (Frontiers in Marine Science, 2023)
The Manila clam (Ruditapes philippinarum) has been introduced into the Atlantic European coast for commercial exploitation. In this region, the population dynamics of this clam species may be determined by the interaction with the native dwarf eelgrass (Zostera noltei). We performed an experiment in the tidal flats of an estuary located in northern Spain to analyse the interaction between Z. noltei and juvenile Manila clams. Based on existing knowledge, it was hypothesised that seagrasses act as a nursery protecting juveniles from predation, which is an important cause of natural mortality, and that seagrass density influences the survival, growth and condition of clams. The results indicate that the effects of seagrasses on juvenile clams depends on shoot density, which mainly determine the relative prevalence of positive versus negative interactions. Dense seagrass meadows protect juvenile clams from predation, likely decreasing their visibility and reducing the efficiency of predators. However, in these dense meadows, a decline in the condition of clams was also observed, although not in shell growth. This decline can be due to the fact that food supply in dense meadows is slow and does not fulfil the replenishment rates required by filter-feeding organisms or because competition for space with the seagrass causes stress. Clams are larger in populations where predator access is prevented, possibly indicating selective predation on larger organisms when this interaction is allowed. The knowledge gained from this experiment is of great interest for analysing possible future trends in clam populations and the derived social implications given its high economic value.